Teacher-student interactions and academic performance of students (Dhaka University Journal of Biological Sciences, 2021)
The main goal of this study was to investigate the influence of teacherstudent interaction on academic performance of the students. Hundred participants (50 teachers and 50 students) were selected through purposive sampling technique to conduct this research. Teacher and student feedback were measured by using the Questionnaire on Teacher Interaction (QTI) as well as students’ academic performance was calculated by using last year grade point average (GPA) of each student. Pearson product moment correlation was used which indicated a positive significant correlation (r = 0.70, p < 0.05) between teacher-student interaction and academic performance of the students. The findings indicated the importance of teacher-student relationships to attain academic success of the students. The results suggest providing appropriate academic resources and aids for the teachers to meet the individual needs of their students.Dhaka Univ. J. Biol. Sci. 30(1): 87-93, 2021 (January)